Anatomical and biochemical responses to oxidative stress in shoots of Bambusa vulgaris Schrad. ex Wendl during the in vitro-ex vitro transition - Garcia, Yudith Yanet; Barrera, Gloria Patricia; Freire, Marisol; Barbón, Raúl; Torres, Sinesio (Research Square, 2024)
Hyperhydricity can affect the development of plant morphology. A better understanding of the anatomical and physiological changes of hyperhydric plants is needed to predict and control the occurrence of hyperhydryc conditions. The aim of this study is to demonstrate the role of oxidative stress in hyperhydricity. To this end, the anatomical, physiological and biochemical responses to oxidative stress in shoots of Bambusa vulgaris Schrad. ex Wendl were compared during the in vitro-ex vitro transition. For this propose, we used shoots grown in two different culture systems: liquid static culture medium and temporary immersion system. Our results showed that hyperhydricity was associated with oxidative stress in the shoots. In hyperhydric shoots chlorophyll content decreased when cultured in liquid static culture medium. Moreover, hydrogen peroxide content and malondialdehyde, as well as the activities of catalase and enzymes of ascorbate-glutathione cycle (ascorbate peroxidase, monodehydroascorbate reductase and dehydroascorbate reductase) were increased in these shoots. On the other hand, scanning electron microscopy showed that the leaves of hyperhydric shoots exhibited anatomical changes in the stomata of the plants, whereas the leaves of normal shoots showed normal structural development. Finally, normal shoots showed high survival rate and allowed better adaptation of the plantlets in the greenhouse.